Development of a web tool to increase research literacy in underserved populations through public library partnerships. - Melissa A Simon; Catherine A O'Brian; Laura Tom; Q Eileen Wafford; Shenita Mack; Samuel R Mendez; Magdalena Nava; Rabih Dahdouh; Rachelle Paul-Brutus; Kathryn H Carpenter; Barbara Kern; Kristi L Holmes (PLoS ONE)
Objective Inadequate diversity in clinical trials is widely recognized as a significant contributing factor to health disparities experienced by racial/ethnic minorities and other diverse populations in the US. To address this in a scalable way, we sought to develop a web tool that could help enhance underserved minority participation in clinical research. Methods We used our research literacy support flashcard tool as the initial prototype for human-centered design and usability testing of the web tool Health for All in public library settings. After forming partnerships with leadership from Chicago Public Libraries (CPL), local medical libraries, and the Chicago Department of Public Health, we conducted seven iterative design sessions with focus groups of library patrons and library staff from six CPL branches serving underserved communities followed by two rounds of usability testing and website modification. Results Based on the qualitative research findings from Design Sessions 1-7, we enacted the design decision of a website that was a hybrid of fact-filled and vignette (personal stories) paper prototypes divided into 4 modules (trust, diversity, healthy volunteers, pros/cons), each with their own outcome metrics. The website was thus constructed, and navigation issues identified in two rounds of usability testing by library patrons were addressed through further website modification, followed by the launch of a beta version of a hybridized single-scrolling and guided module prototype to allow further development with website analytics. Conclusions We report the development of Health for All, a website designed to enhance racial/ethnic minority participation in clinical trials by imparting research literacy, mitigating distrust engendered by longstanding racism and discrimination, and providing connections to clinical trials recruiting participants.